2009
DOI: 10.4314/ejesm.v2i2.45918
|View full text |Cite
|
Sign up to set email alerts
|

Economic Reforms, Living Conditions and Urban Violence: A Situation Analysis of Metropolitan Lagos

Abstract: Abstract.Urban poor have suffered significantly from structural adjustment through reduction in employment creation and downward pressure on real wages. The precarious effects of fluctuation in the formal and informal sectors on urban men and women are seldom noticed in the upsurge of urban violence and conflicts. The study specifically examined the impact of privatization and commercialisation on social conditions and livelihood of urban people as the cause of gender differentials in urban violence. Metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study from the area of metropolitan Lagos, it was found that 77% of the randomly selected respondents lived in houses where 5–10 people shared the same sleeping room (Adeyemi et al ., 2009 ). Crowding in Lagos is the result of factors such as a low standard of living, migration to find a means of survival and religious and culturally dependent attitudes emanating from having many children to help out with agricultural livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…In a study from the area of metropolitan Lagos, it was found that 77% of the randomly selected respondents lived in houses where 5–10 people shared the same sleeping room (Adeyemi et al ., 2009 ). Crowding in Lagos is the result of factors such as a low standard of living, migration to find a means of survival and religious and culturally dependent attitudes emanating from having many children to help out with agricultural livelihoods.…”
Section: Introductionmentioning
confidence: 99%